Difficulties in communication of doctors in care for the deaf person (Research, Society and Development, 2022)
Objective: To investigate communication difficulties in medical care for the deaf public in different health services. Methodology: Quantitative and descriptive study with medical professionals who work in different health services in the city of Mineiros - GO, through the application of a semi-structured questionnaire, composed of 25 questions. Results: Most of the doctors surveyed did not have the Libras discipline in their academic formation. Even so, they think it is important to include this subject in undergraduate courses and believe that the lack of knowledge of the language can influence the diagnosis/treatment of the patient. Many reported having difficulty communicating and feeling embarrassed during the consultation with the deaf patient. Conclusion: It is noticed the importance of knowledge of Libras for humanized and quality care to the deaf patient, however, most doctors do not have this knowledge.